Merawat Kebersamaan melalui Tradisi Slametan dan Makan Bersama di Hari Raya Iduladha Masyarakat Kabupaten Pekalongan - Nahla Asyfiyah; Fatma Fauziyah; Klaudia Siti Nur Azizah; Vika Aulia Safitri; Dimas Setiaji Prabowo (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study aims to analyze the implementation of the slametan and communal dining traditions after the Eid al-Adha prayer in Gumawang and Mrican Villages, Pekalongan Regency, and to examine their role in strengthening social relations within the community. This research employed a descriptive qualitative method with a cultural studies approach. Data were collected through field observations, interviews, and documentation analysis to explore the meaning, practices, and social functions of the tradition. The findings reveal that the slametan tradition reflects a harmonious acculturation between Islamic values and Javanese cultural practices. In Gumawang Village, the tradition is characterized by the implementation of tahlilan and adaptations in food presentation, shifting from heavy meals to lighter snacks according to contemporary community conditions. Meanwhile, in Mrican Village, communal dining serves as a social equalizer through voluntary contributions of food that overcome differences in economic status, supported by organized mutual cooperation (gotong royong) involving both men and women. This tradition plays an important role as a social medium for maintaining solidarity, strengthening interpersonal relationships, preserving cultural identity, and preventing social conflicts in the context of modern society.